2013
DOI: 10.1371/journal.pone.0057776
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Urinary Tract Infections in Gaborone, Botswana

Abstract: ObjectiveThe microbiology and epidemiology of UTI pathogens are largely unknown in Botswana, a high prevalence HIV setting. Using laboratory data from the largest referral hospital and a private hospital, we describe the major pathogens causing UTI and their antimicrobial resistance patterns.MethodsThis retrospective study examined antimicrobial susceptibility data for urine samples collected at Princess Marina Hospital (PMH), Bokamoso Private Hospital (BPH), or one of their affiliated outpatient clinics. A ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…We collected 433 bacterial strains from cases of UTI in inpatients. The resistance rate at our hospital is similar to that reported in domestic research [18] and is higher than that found reported abroad [19,20]. In our study, the resistance rates for quinolones and cotrimoxazole, which are commonly used in UTI, were higher than 40%, except for Enterobacter cloacae .…”
Section: Discussionsupporting
confidence: 86%
“…We collected 433 bacterial strains from cases of UTI in inpatients. The resistance rate at our hospital is similar to that reported in domestic research [18] and is higher than that found reported abroad [19,20]. In our study, the resistance rates for quinolones and cotrimoxazole, which are commonly used in UTI, were higher than 40%, except for Enterobacter cloacae .…”
Section: Discussionsupporting
confidence: 86%
“…(Francesco et al, 2007; Pires et al, 2007; den Heijer et al, 2012; Mukherjee et al, 2013; Prakash and Saxena, 2013; Renuart et al, 2013). Extended spectrum β-lactamase (ESbL)–producing organisms causing a significant increase in infection outbreaks have been reported in every continent around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Primary health care is available in the region; antibiotics can be acquired freely over the counter and resistance to many first-line antimicrobials is common (Rowe et al 2010;Pesapane et al 2013;Renuart et al 2013). There are no commercial livestock or poultry production operations in the region.…”
Section: Introductionmentioning
confidence: 99%